P ( 2 1 ) − P ( 3 ) = B A − C ln 3 + E D ln 2
Let P ( a ) , a > 0 be the probability that for two real numbers x , y chosen uniformly at random from the interval [ − a , a ] it is the case that x y > ( x + y ) .
If the equation above holds true for positive integers A , B , C , D and E with g cd ( A , B ) = g cd ( D , E ) = 1 , find A + B + C + D + E .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Great! Thanks for posting your solution. :)
In general P ( a ) = 4 1 + 2 a 1 − 2 a 2 ln ( a + 1 ) for 0 < a ≤ 2 and 2 1 − 2 a 2 ln ( a 2 − 1 ) for a ≥ 2 .
Problem Loading...
Note Loading...
Set Loading...
For x y > ( x + y ) we must have x y − x − y + 1 > 1 or ( x − 1 ) ( y − 1 ) > 1 . Letting m = x − 1 and n = y − 1 P ( a ) is the probability that m n > 1 or m > n 1 for m , n chosen uniformly at random in the interval [ − a − 1 , a − 1 ] . For P ( 2 1 ) this is m > n 1 in the interval [ − 2 3 , − 2 1 ] which, as both will be negative is the same as considering the interval [ 2 1 , 2 3 ] . Graphically this is simply the integral ∫ 3 2 2 3 ( 2 3 − n 1 ) d n = 4 5 − l n ( 3 ) + 2 l n ( 2 ) divided by the total area contained by this interval which is ( 2 3 − 2 1 ) 2 = 1 so P ( 2 1 ) = 4 5 − l n ( 3 ) + 2 l n ( 2 ) . For P ( 3 ) we can apply the same concept, splitting it into cases. Here we have m , n in the interval [ − 4 , 2 ] it is clear that for their product to be over 1 they must either both be positive or both be negative. When they are both positive with m , n in the interval [ 0 , 2 ] the integral is graphically ∫ 2 1 2 ( 2 − n 1 ) d n = 3 − 2 l n ( 2 ) . When they are both negative in the interval [ − 4 , 0 ] this is equivalent to the interval [ 0 , 4 ] , thus the integral is ∫ 4 1 4 ( 4 − n 1 ) d n = 1 5 − 2 l n ( 4 ) . These two cases summed is 1 8 − 6 l n ( 2 ) but this must be considered out of the total area contained by the interval [ − 4 , 2 ] which is ( 2 − ( − 4 ) ) 2 = 3 6 so P ( 3 ) = 3 6 1 8 − 6 l n ( 2 ) = 2 1 − 6 1 l n ( 2 ) . Subtracting this from P ( 2 1 ) gives P ( 2 1 ) − P ( 3 ) = 4 3 − 2 l n ( 3 ) + 6 1 3 l n ( 2 ) so A + B + C + D + E = 3 + 4 + 2 + 1 3 + 6 = 2 8